2013
DOI: 10.6090/jarq.47.405
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simulated Sea Level on the Sedimentation of the Tien River Estuaries, Lower Mekong River, Southern Vietnam

Abstract: Owing to global warming, sea-level rise (SLR) poses a serious threat to low-lying coastal areas. The potential impacts of SLR include inundation, coastal erosion, salinity intrusion, and degradation of coastal habitat. The Mekong River Delta (MRD) in southern Vietnam is a flat, low-lying land area that has experienced significant effects of climate change and SLR. Sea-level data collected from 1979 to 2006 show that the highest mean surface level of the spring tide has risen by 13 cm. This study investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…When the bed shear velocity exceeds the fall veloctiy, sediment is transported as both suspended sediment and bed load. The sediment properties specified in the model are presented Table 1, which are based on a number of previous studies, Hung et al [8], Manh et al [15], Ngoc et al [1]. Most suspended sediment in the LMD is fine-grained, Hung et al [7].…”
Section: Mike 11 St Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…When the bed shear velocity exceeds the fall veloctiy, sediment is transported as both suspended sediment and bed load. The sediment properties specified in the model are presented Table 1, which are based on a number of previous studies, Hung et al [8], Manh et al [15], Ngoc et al [1]. Most suspended sediment in the LMD is fine-grained, Hung et al [7].…”
Section: Mike 11 St Modelmentioning
confidence: 99%
“…A large number of sedimentation studies were conducted and published, Steiger et al [20], [21], Middelkoop [22], Baborowksi et al [23], Hung et al [7] [8] [13], Manh et al [14] [15], Ngoc et al [1], Habersack et al [24], however, these studies focused on other aspects such as reservoir sedimentation, urban retention pond, reservoir influence or suspended sediment mobilization and transport in small mountainous catchments. Then, the sediment transport (ST) model is used to compute spatial variation of sediment erosion and deposition in the river/channel network of the LMD.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the impacts of waves and salinity were not considered in detail, and sediment transport and bed parameters were not determined by measured data. In the study of Ngoc et al (2013), two large-scale models were established to investigate the impacts of climate change and SLR on sedimentation processes in the Tien River estuary. Ngoc et al (2013) showed that morphological evolutions would become too complex to estimate in case of rising sea levels.…”
Section: Introductionmentioning
confidence: 99%